Cissus quadrangularis L. hexane extract infused glyoxal cross-linked chitosan-collagen scaffold elicits early osteoinduction - Praseetha R. Nair; P.S. Unnikrishnan; Sachin J. Shenoy; G.S. Sailaja (Phytomedicine Plus)
Background: The induction of osteoblast activity by natural materials would possibly eliminate toxicity concerns and can serve as a better approach for regenerative drug development studies. Cissus quadrangularis Linn. (CQ) extract is a good source of β-sitosterol, phytoestrogens, β-carotene, flavonoids, etc., and aqueous CQ extract is traditionally used for bone fracture healing. Purpose: This study presents histopathological evidence for the significant osteoinductive potential of CQ hexane extract in a mechanically reinforced natural scaffold in rat models of critical sized calvarial defects. Study design: To validate the bone regeneration potential of glyoxal cross-linked, mechanically reinforced, CQ hexane extract-infused chitosan-collagen scaffold (CHCOHE) in vivo in a critical-size rat calvarial defect model. (Controls: SHAM (defect without scaffolds) operated control and chitosan collagen scaffold (CHCO)). Materials and methods: Glyoxal cross-linked chitosan-collagen scaffold is prepared as per the procedure we have reported recently. A critical-size defect (6 mm diameter × 2 mm thickness) was made at the dorsal calvarium using a trephine burr. The 6 mm critical sized calvarial defects were created and the scaffolds (CHCOHE and CHCO) were implanted into the defect. SHAM served as a negative control. The animals were sacrificed after 4 and 12 weeks to analyze the extent of new bone formation. Results: Histopathological evaluation of CHCOHE implanted critical-size calvarial defect in rats indicates the presence of osteoblast cells, neovascularization along with evidence of scaffold degradation by giant cells after 4 weeks. Continual examination designates the formation of mature lamellar bone formation at 12 weeks both in the middle and periphery regions of the defect site. Although CHCO scaffold alone also promoted healing, the quantitative assessment of new bone formation is significantly greater for CHCOHE than CHCO group. SHAM-operated controls did not elicit any new bone formation. Conclusion: This study highlights the high competency of CQ hexane extract (even at a very low concentration) and the efficacy of glyoxal cross-linked chitosan-collagen natural scaffold as a potential osteoinductive biodegradable scaffold for repairing critical-size bone defects.